Genetic Analysis and Character Association in Jamir (Citrus jambhiri) Accessions of Bangladesh by Using Morphological Traits (Progressive Agriculture, 2013)
An experiment was carried out to study the morphological variability, characters association, correlation and path coefficient analysis of 14 Jamir accessions during the period from January 2007 to March 2008. Significant variations were observed for all the plant characters studied. The accession CJ09 was characterized with the maximum plant height (6.20m), spreading of branch (north-south 4.90 m and east-west 4.87m), base girth (58cm), plant growth (102.76m3), tree volume (24.64m3) and segment length (9.70). The accession CJ15 showed maximum spine length (25.33mm), CJ05 was characterized with high lamina area (14.94cm3). The accession CJ12 showed the highest % fruit set (36.67%). The highest fruit weight (1753.33g), fruit diameter (46cm), rind thickness (2.73cm) was observed in CJ11. The accession CJ09 was characterized with maximum number of segment (15.33) and pulp weight (746.67). Maximum TSS (12.20%) was found in CJ12. The accession CJ09 was characterized with minimum number of seeds (14). Correlation coefficient study indicated that fruit diameter, rind thickness, length of segment and number of segment had positive and highly significant phenotypic association with fruit weight and also genotypic positive association. Percent Fruit set had negative genotypic and phenotypic association with fruit weight. In respect of path analysis, fruit diameter, rind thickness, number of segment, length of segment contributed to maximum phenotypic and genotypic direct effects on fruit weight indicating their importance as selection parameters.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16843 Progress. Agric. 20(1 & 2): 17 26, 2009